Pengaruh Word of Mouth, Promosi dan Citra Sekolah terhadap Keputusan Orang Tua Siswa Memilih Sekolah SMP Santu Petrus Pontianak - Gita, Yolanda Maya; Widodo, Teguh; Fathorrahman, Fathorrahman (SENTRI: Jurnal Riset Ilmiah, 2026)
Increasing competition among educational institutions requires schools to implement effective marketing strategies to attract prospective students and their parents. SMP Santu Petrus Pontianak, as one of the leading private junior high schools in Pontianak City, faces increasing competition from schools offering various educational advantages. This study aims to analyze the influence of word of mouth, promotion, and school image on parents’ decision to choose SMP Santu Petrus Pontianak. A quantitative approach with a causal research design was employed. The study involved 218 parents selected through purposive sampling. Data were collected using structured questionnaires and analyzed using the Structural Equation Modeling–Partial Least Squares (SEM-PLS) method with SmartPLS software. The results indicate that word of mouth has no significant effect on parents’ school choice decisions (β = -0.051; p = 0.360). In contrast, promotion has a positive and significant effect (β = 0.222; p < 0.001), while school image has the strongest positive and significant effect (β = 0.726; p < 0.001). The R-square value of 0.710 indicates that the three variables explain 71.0% of the variance in parents’ school choice decisions. These findings demonstrate that strengthening school image and implementing effective promotional strategies are essential for increasing school competitiveness and influencing parents’ decisions in selecting a school.